Orfeu sem travessa: leitura de um poema de José Paulo Paes - Pires, Antônio Donizeti [UNESP] (My University, 2013)
Starting from general considerations on the Orpheus myth and its resonance on Brazilian poetry, this essay aims at an interpretative analysis of the prose poem “Orpheus” from José Paulo Paes, published in one of the author’s latest books, A meu esmo (1995).

A partir de considerações gerais sobre o mito de Orfeu e suas ressonâncias na poesia brasileira, este ensaio objetiva uma análise interpretativa do poema em prosa “Orfeu”, de José Paulo Paes, publicado num dos últimos livros do autor, A meu esmo (1995).
Orpheus without crossings: a reading of a José Paulo Paes’s poem
Keywords: Brazilian poetry; Contemporaneity; Lyric poetry; Orpheus myth; Poetic analysis; Poesia brasileira contemporânea; Análise do texto poético; Orfeu e orfismo